A simplified suturing model for preclinical training - Ramesh Kumaresan; Sivakumar Pendayala; Balamanikanda Srinivasan; Kameswari Kondreddy (Wolters Kluwer Medknow Publications, 2014)
Objectives: The purpose of this paper is to develop a simple and cost-effective suturing training model. Materials and Methods: A simplified suturing model is developed for preclinical training purpose. The training model requires only three easily available materials, which include synthetic foam sponge, elastomeric impression material and putty impression material. Construction of this model requires only 15 min. Results: The training model thus developed resembles a realistic human tissue with a skin analog, deeper connective tissues and a bony base. This enables the students to practice various suturing technique at different tissue planes. Such practice helps the students to perform a live procedure in a more skilled and less traumatic way. Conclusion: The easy availability and cost-effective nature of the materials, in concert with fast construction time, makes this suturing model appropriate when an affordable alternative is desired.